If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 4r + -1 = 7r + 7 + -2r Reorder the terms: 4 + -1 + 4r = 7r + 7 + -2r Combine like terms: 4 + -1 = 3 3 + 4r = 7r + 7 + -2r Reorder the terms: 3 + 4r = 7 + 7r + -2r Combine like terms: 7r + -2r = 5r 3 + 4r = 7 + 5r Solving 3 + 4r = 7 + 5r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-5r' to each side of the equation. 3 + 4r + -5r = 7 + 5r + -5r Combine like terms: 4r + -5r = -1r 3 + -1r = 7 + 5r + -5r Combine like terms: 5r + -5r = 0 3 + -1r = 7 + 0 3 + -1r = 7 Add '-3' to each side of the equation. 3 + -3 + -1r = 7 + -3 Combine like terms: 3 + -3 = 0 0 + -1r = 7 + -3 -1r = 7 + -3 Combine like terms: 7 + -3 = 4 -1r = 4 Divide each side by '-1'. r = -4 Simplifying r = -4
| x=-21+16 | | 50=14+2x | | 4x+2=6x+30 | | -7a-15+-4a+18= | | 4v+24=-3(6v-6)+4v | | 5/4(8) | | 3(-6)+6=2(-6) | | 3p+11p=28 | | 5x-6x=8-2x | | Y=4(-5.25)+25 | | 4x+25=4 | | y/17=-11 | | 4.75=9.5-3/4x | | 9x+4=7+5x | | f/12=12/16 | | 2/3/1/13 | | Y=-3(3)+12 | | 0=9.5-3/4x | | -17/2(-20)+60 | | (a+b/c)(d-e)=f | | -17/4(-20) | | 2x-3=3x+12 | | x+0.02=870 | | 2x+16=42 | | -17/4(-20)+60 | | 2x+17=39 | | -5(2b+1)+(11b-7)=0 | | -1=5+n | | 72=3x(x+2) | | 1.3q-3.8-5.6q=-5.3q-4.3 | | 130=10x+7y | | -14=-7m |